(untitled) (Indian Journal of Geo-Marine Sciences (IJMS), 2025)
A massive bloom of Trichodesmium (T. erythraeum and T. thiebautii) was observed in the coastal waters of Kalpakkam, southeast India. The bloom formed thick and greenish-yellow patches on the sea surface during the post-monsoon season (March 2020). Water and plankton samples were collected in Coastal Near-shore (CNW) and Coastal Offshore Waters (COW) at 12 stations. Nitrate and phosphate concentrations were found distributed evenly in the entire study site. Concentration of ammonia and total nitrogen found increased significantly during the bloom period as compared to non-bloom periods. The blooming species T. erythraeum and T. thiebautii contributed 53.98 % and 43.82 % to the region’s phytoplankton population density. Phytoplankton and zooplankton species richness was relatively low during the study. Results indicated that the higher temperature (≥ 29 °C) and constant salinity (≥ 33 PSU) are the conducive factors for Trichodesmium growth. The MODIS Aqua satellite-derived Sea Surface Temperature (SST) and chlorophyll data further supported the in-situ observations.